Relationship Between Risk Factors of Coronary Heart Disease on The Amount of Lesioned Coronary Artery - Monitrya Nababan; Achmad Lefi; Djohar Nuswantoro (Health Notions, 2019)
Objective: To determine the relationship of coronary heart disease traditional risk factors to the number of lesioned coronary arteries and calculate the relative risk. Methods: This study used an analytical research design with a retrospective cohort study design using patient catheterization report data. Data analysis was performed using the chi square test and relative risk in 449 individuals. Results: Based on the analysis results obtained p value 0.05 indicating no relationship between risk factors for coronary heart disease with the number of coronary arteries the lesions based on sex, history of hypertension and history of smoking. Conclusion: There is a relationship between age, history of diabetes mellitus, history of dyslipidemia and the number of coronary arteries that are lesions in patients with coronary heart disease and there is no relationship between sex, history of hypertension and smoking history with the number of coronary arteries that are lesions in patients with coronary heart disease. Keywords: single vessel disease; multivessel disease; coronary artery disease; risk factors CAD